Experimental and numerical investigation on the saw-tooth connector subjected to compressive load. (March 2021) - Al-kroom, Hussein; Reimer, Andreas; Alghrir, Yassin; Thneibat, Mujahed; Schmid, Volker
Abstract: The saw-tooth connector is a device for high-capacity load transfer between steel and concrete. It is an embedded steel plate with a toothed outline which provides an extensive surface for contact pressure between the two materials. The connector creates an alternative to headed shear studs and perfobond rib shear connectors in composite structures. This study explores the behavior of the connector fixed in the middle of slender reinforced concrete slabs through an experimental and analytical method. The results of a modified push-out test show that the saw-tooth connector is capable of transferring higher load than the conventional shear connectors. However, its failure is described as brittle. A three-dimensional finite element model is developed to capture the right behavior of the connection and predict the shear force of the connector. The verified FE-model indicates that the failure of the connection between the concrete and the connector is caused by the deterioration of the strength of concrete around the comparably higher loaded end of the connector. Thus, the strength of the concrete governs the load capacity of the saw-tooth connector. Parametric study is conducted by the verified finite element model. The study investigates the effects of changing different variables on the force transferred by the connector. The parametric study shows that the load capacity of the connector is affected by changing the thickness exclusively of the slab or the slab and the connector conjoined. Nevertheless, the displacement of the saw-tooth connector remains almost the same. On the other hand, changing the length of the connector affects both the load capacity and the displacement of the connector. Formulas to predict the maximum shear resistance of the connector are proposed. The formulas are developed based on the results attained from the parametric study and the experiments. Graphical abstract: Unlabelled Image Highlights: A high-capacity saw-tooth connector is employed to transfer the load into the slender reinforced concrete slabs. The saw-tooth connector is subjected to a compressive monotonic load to observe the connector's maximum bearable force. An Advanced 3D finite element model is developed to assess the behavior of the connector. An analytical approach is proposed to predict the connector's strength under compressive loading in the middle of the slab.